Rhamnogalacturonate Lyase RhiE Is Secreted by the Out System in Erwinia chrysanthemi - Laatu, Minna (American Society for Microbiology, 2003)
Supernatants of rhamnose-induced Erwinia chrysanthemi strain 3937 cultures contain a principal secreted protein named RhiE. A rhiE mutant has been found among a set of rhamnose-induced MudI1681 lacZ fusions. RhiE is a 62-kDa protein that has rhamnogalacturonate lyase activity on rhamnogalacturonan I (RG-I). It does not require a divalent cation for its activity and has an optimal pH of 6.0. rhiE expression is strongly induced in the presence of rhamnose but is also regulated by PecT and Crp, two regulators of the transcription of pectinolytic enzyme genes. RhiE is secreted through the type II Out secretion pathway. RhiE has no disulfide bond. The absence of RhiE secretion in a dsb mutant indicated that disulfide bond formation is required for the biogenesis of the secretion apparatus. RhiE was searched for in several E. chrysanthemi strains by using antibodies, and it was found to be present in one-third of the strains tested. However, the reduced virulence of the rhiE mutant indicates that degradation of the RG-I region of pectin is important for full virulence of E. chrysanthemi.